Plasma confinement by means of poloidal-toroidal magnetic surfaces - Maksyuta, M.V.; Golovach, G.P.; Martysh, Ye.V. (Вопросы атомной науки и техники, 2011)
The paper proposes to perform plasma magnetic confinement in the constructions where plasma streams flow by knotted trajectories. It is shown that in this case due to more complicated topology of plasma circulation, a quasi-stationary equilibrium may be carried out without an external magnetic field, and i.e. plasma is self-confined by the self-generation of poloidal-toroidal magnetic surfaces. This phenomenon may serve as a mechanism of a ball-lightning origination and existence. Пропонується магнітне утримання плазми здійснювати в таких конструкціях, в яких плазмові потоки рухаються завузленими траєкторіями. Показується, що в цьому випадку за рахунок більш складної топології циркуляції плазми квазістійка рівновага може існувати і без зовнішнього магнітного поля, тобто плазма утримує сама себе за допомогою породжуваних нею полоїдально-тороїдальних поверхонь. Це явище може слугувати механізмом виникнення та існування кульової блискавки. Предлагается магнитное удержание плазмы осуществлять в конструкциях, в которых плазменные потоки движутся заузленными траекториями. Показывается, что в этом случае за счет более сложной топологии циркуляции плазмы квазиустойчивое равновесие может существовать и без внешнего магнитного поля, т.е. плазма удерживает сама себя с помощью порождаемых ею полоидально-тороидальных магнитных поверхностей. Это явление может служить механизмом возникновения и существования шаровой молнии.